2017
DOI: 10.7567/jjap.56.06gj02
|View full text |Cite
|
Sign up to set email alerts
|

Tuning porosity and radial mechanical properties of DNA origami nanotubes via crossover design

Abstract: DNA origami nanotubes are utilized as structural platforms for the fabrication of various micro/nanosystems for drug delivery, optical or biological sensing, and even nanoscale robots. Their radial structural and mechanical properties, which play a crucial role in the effective use of micro/nanosystems, have not been fully studied. In particular, the effects of crossovers, which are basic structures for rationally assembling double-stranded DNA (dsDNA) helices into a nanotube configuration, have not yet been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…[30][31][32][33][34][35][36][37][38][39] Therefore, DNA origami design choices such as lattice type, staple lengths, crossover location and spacing, twist correction, and so on all affect the structural and mechanical properties and thus the environment-dependent behavior of the nano structures. [25,37,[39][40][41][42][43][44][45][46] This means DNA stability can be manipulated also by rational design, instead of solely by outer factors. For example, deliberate design can be used for additional benefit in devising tools like drug carriers with engineered release profiles.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39] Therefore, DNA origami design choices such as lattice type, staple lengths, crossover location and spacing, twist correction, and so on all affect the structural and mechanical properties and thus the environment-dependent behavior of the nano structures. [25,37,[39][40][41][42][43][44][45][46] This means DNA stability can be manipulated also by rational design, instead of solely by outer factors. For example, deliberate design can be used for additional benefit in devising tools like drug carriers with engineered release profiles.…”
Section: Introductionmentioning
confidence: 99%
“…29 The moduli associated with radial compression of rod-like origamis have also been probed by atomic-force microscopy. 39 Most explorations of the mechanical limits of DNA origami have focused on the effects of tension typically applied by optical tweezers or an atomic-force microscope. [40][41][42][43] These studies have revealed saw-tooth force-extension profiles, where the origamis yield through multiple unravelling events.…”
Section: Introductionmentioning
confidence: 99%
“…Paul Rothemund utilized multiple branched junctions as structural motifs to fold single stranded bacteriophage DNA, M13mp18, creating the DNA origami technique (Figure 10a). [117,118] Peng Yin developed the self-assembly of DNA tiles and bricks to further expand the rapidly growing number of structures that can be made using short DNA oligonucleotides (Figures 10b and 10c). The precise placement of ligands has enabled development of 'molecular pegboards' as tools to study individual molecular interactions, distance requirements, and enzymatic cascades.…”
Section: A U T H O R Accepted Manuscriptmentioning
confidence: 99%